Digitized records in the archives of Bosnia and Herzegovina - protection and accessibility - Domazet, Siniša (Moderna arhivistika, 2019)
In 2018, the Archive of Bosnia and Herzegovina digitized for the first time acomplete fond -the BiH Religious Affairs Commission. Thisparticularfond was selected because it was highly sought after, had no backups and consisted of only 114archivalboxes, which is the appropriate volume for the pilot project. In addition, the documents have been processed with an OCR program (it is necessary to manually enter certain corrections though). Once stored in the database, it was possible to be simultaneously used by several researchers from different locations and without contact with the originals. Suddenly, it has become simply unthinkable that until yesterday a technician had to go to the depot to fetch requested document. Almostunthinkable. The remaining 99% of the fonds are still processed by conventional methods. However, the example of the Religious Affairs Commissiondemonstrated in practice what kind of a bright future awaits the archives, afterthey master their first clumsy steps toward full digital maturity.This paper presents current progress in the Archives of Bosnia and Herzegovina and its efforts to move forward with this demanding process, since the digital archive has been recognized as an indispensable part of the time to come.
Keywords: access; database; digitalizacija; digitization; dolgoročno ohranjanje podatkov; dostop; long term data preservation; podatkovna baza; scanning; zajem